THE APPLICATION OF MAKE A MATCH LEARNING MODEL IN IMPROVING STUDENT LEARNING OUTCOMES IN SCIENCE - Yuliana Yenita Mete; Ainun Jariyah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
Based on the observation, the problem found in class IV SDK Nangakeo was that the low achievement on students learning outcomes due to the learning method used are more passive which cause the learning atmosphere becomes not conducive. In order to solve this problem, the teacher applies the make a match learning model. The aim is to find out the improvement of students learning outcomes in the science subject with the topic of plant leaf structure and its function in the Nangakeo SDK, Ende Regency. The implementation process using the Classroom Action Research (CAR) model consists of four stages namely planning, implementation, observation, and reflection. Data collected through observation, interviews and tests. Data analysis techniques used quantitative descriptive analysis techniques. After analyzing, the results of the study showed that cycle I had an average of 58.10 with a percentage of completeness of 31.57% and the results of cycle II had increased to 84.94 with 100% completeness. Based on these results it can be concluded that the application of the make a match learning model can improve student learning outcomes.